Pancreatic Heterotopia in the Gallbladder Associated with Chronic Cholecystitis: A Rare Combination - Al-Shraim, Mubarak; Rabie, Mohammad Ezzedien; Elhakeem, Howaida; Kandeel, Ahmad; Shah, Mian Tahir; Jamil, Salim (JOP. Journal of the Pancreas, 2010)
Context Pancreatic heterotopia is a rare pathologic entity, previously reported in the stomach, duodenum and jejunum. It is mostly asymptomatic and rarely gives rise to complications. Localization of pancreatic heterotopia in the gallbladder is extremely rare and can be associated with cholecystitis or cholecystolithiasis. Case report We herein describe a case of a 39-year-old man who presented with biliary type pain with ultrasonographic evidence of a gallbladder polyp. Laparoscopic cholecystectomy was performed with uneventful recovery. Pathologic examination of the gallbladder detected a heterotopic focus of pancreatic tissue in its wall, associated with chronic cholecystitis with no gallstones. Conclusion Pancreatic heterotopia of the gallbladder is a very rare entity with unknown clinical significance. Awareness of this condition may facilitate its recognition which may shed more light on its clinical significance. Image: Features of chronic cholecystitis and pancreatic heterotopic tissue.